Examining Responsible Tourism Experience of Thai Tourists in Salak Khok, Trat - Pataratanakobkul, Yosita; Damchoo, Paramet (Journal of Business, Innovation and Sustainability (JBIS), 2023)
The objectives of the study were to investigate the experience of tourists in responsible tourism at Salak Khok, Trat and to propose guidelines for creating a responsible tourism experience. This study was an in-depth interview research. The population was Thai tourists who gained travel experience at Slak Khok, Trat. A sample was selected from 30 cases using convenience sampling. The findings showed the tourists gained responsible experiences through Mad boat tour activity by interacting with local people and learning in culture, social and environment consciousness by experienced with local tourism management. The tourist experiences affected their responsible behavior in travel. Based on the findings, it was recommended about guidelines for creating a responsible tourism experience as follows: 1) Creating an experience beyond the expectations of tourists through local communication and encouraging tourists to take part in creating responsibility. 2) Creating an understanding of responsible tourism for tourists through the participation of the people in the community and clarification of practices to tourists. and 3) Creating tourism management within the community through local storytelling skills and tourism public relations.